2006 IEEE 4th World Conference on Photovoltaic Energy Conference 2006
DOI: 10.1109/wcpec.2006.279775
|View full text |Cite
|
Sign up to set email alerts
|

High-Efficiency P-I-N Microcrystalline and Micromorph Thin Film Silicon Solar Cells Deposited on LPCVD Zno Coated Glass Substrates

Abstract: The authors report on the fabrication of microcrystalline silicon p-i-n solar cells with efficiencies close to 10%, using glass coated with zinc oxide (ZnO) deposited by low pressure chemical vapor deposition (LPCVD).LPCVD front contacts were optimized for p-i-n microcrystalline silicon solar cells by decreasing the free carrier absorption of the layers and increasing the surface roughness. These modifications resulted in an increased current density of the solar cell but also in significantly reduced fillfact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
96
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(99 citation statements)
references
References 4 publications
2
96
0
Order By: Relevance
“…Although ''cracks'' have been reported in the past by several authors [11][12][13][14], their full role in limiting the device performance has only been evidenced recently [15][16][17][18]. In our laboratory, mc-Si:H p-i-n solar cells are deposited on glass covered by low pressure chemical vapor deposition zinc oxide (LPCVD ZnO), which possesses a natural texture, with as-grown pyramids at the surface, exhibiting typically a V-shape structure [19,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although ''cracks'' have been reported in the past by several authors [11][12][13][14], their full role in limiting the device performance has only been evidenced recently [15][16][17][18]. In our laboratory, mc-Si:H p-i-n solar cells are deposited on glass covered by low pressure chemical vapor deposition zinc oxide (LPCVD ZnO), which possesses a natural texture, with as-grown pyramids at the surface, exhibiting typically a V-shape structure [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…An existing approach to decrease crack density is to modify the surface morphology from V-shape to U-shape by applying a surface treatment [14,21]. However, the surface treatment decreases the light scattering capabilities of the LPCVD ZnO [22] because of the change in morphology.…”
Section: Introductionmentioning
confidence: 99%
“…To optimize the morphology for the growth of the cells, the ZnO surface was treated for 20 min with an argon plasma. 32 A negative UV-NIL stamp was fabricated by nanoimprinting of the master ZnO texture into a UV sensitive sol-gel lacquer (Ormocer from Micro Resist Technology GmbH). After curing under UV light and demolding, this stamp was coated with an antisticking layer and used to transfer the positive structure onto a UV-NIL lacquer on a borosilicate glass substrate.…”
mentioning
confidence: 99%
“…In order to fill this gap, we base our understanding on previous work showing that the morphology observed at the surface of LP-MOCVD ZnO results from a combination of both nucleation-and kinetic-driven phenomena [8][9][10][11][12][13][14][15][16][17]. In fact, it was demonstrated that temperature induced inter-facet diffusion could lead to the selection of different crystallographic PO [8].…”
Section: Discussionmentioning
confidence: 99%
“…As-grown LP-MOCVD ZnO presents V-shaped valleys separating the pyramidal features, which causes defective mc-Si growth, leading to decreased open-circuit voltage (V oc ) and fill factor (FF), and hence to lower cell efficiency [10]. One possible approach to circumvent these issues is to use a surface plasma treatment to transform the V-shaped valleys into smoother U-shaped valleys that are well-adapted for good-quality absorber material deposition [11]. However, such plasma treatment leads to a decrease in the scattering ability of the film.…”
Section: Introductionmentioning
confidence: 99%